A materialização da dignidade da pessoa humana e o cumprimento das penas privativas de liberdade - Paiva, Uliana Lemos de (2012)
The current research come from need to analyze possibilities to materialize human dignity principle during freedom curtail penalties fullfilment, abreast finding that internal and international regulations dictate this is the way to be tread by Brazilian penitentiary system, however, verily, indignity, assistance missing, overcrownding, crime, in the end, barbarie reigns. The work will analyze two strands in order to effective the mentioned principle: the state responsability optics, such in internal scope, as internationally, abreast historical omission in satisfy Constitution, international treaties and laws; and also indicating penal execution alternative methods adoption as a way, bringing to fore a case study - called "apaqueano" method. With such desideratum will bring, first of all, considerations about consolidation process of human dignity principle, its concept and essential content. Furthermore, will address historical and philosophical evolution of freedom curtail penalties. As it follows, will be done an approach about constitutional and underconstitutional legislation that disciplines penalties fullfiling in Brazil, analyzing their main aspects, emphasizing the possibility to charge Brazilian state for disregarding mentioned standards. Next, will also be started a critical analyzis about international regulations, which forbids diminishing or cruel penalties or treatments, approaching human rights international treaties and conventions ratified by Braziland their incorporation and effectiveness in local Law, emphasizing monitoring forms and country international charging possibility for disregarding international regulations. Lastly, will advance to the real possibility to materialize human dignity principle in penalties fullfiling, based in a case study verification - the APAC (Associação de Proteção e Assistência aos Condenados) called method, analyzing the various theories about penalties grounding, with emphasis in their ressocializing function, as well as traditional penitentiary systems, and the theory adopted by vernacular order, in desideratum to contribute to improve national penitentiary system chaotic situation